1992
DOI: 10.1063/1.860017
|View full text |Cite
|
Sign up to set email alerts
|

Critical error fields for locked mode instability in tokamaks

Abstract: Otherwise stable discharges can become nonlinearly unstable to disruptive locked modes when subjected to a resonant m =2, n= 1 error field from irregular poloidal field coils, as in DIII-D [Nucl. Fusion 31, 875 (1991)], or from resonant magnetic perturbation coils as in Experiments in Ohmically heated deuterium discharges with q-3.5, n z 2 x 1019 me3 and BT z 1.2 T show that a much larger relative error field (Br21/BT =: 1 X 10e3) is required to produce a locked mode in the small, rapidly rotating plasma of CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
137
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(147 citation statements)
references
References 12 publications
8
137
2
Order By: Relevance
“…(a) Helical field penetration: For the plasma being originally stable to tearing modes, an applied resonant helical field (or error fields of experimental devices) can penetrate through the resonant surface and generate a magnetic island there [1][2][3][4][5][6][7][8][9]. Recently it was shown on TEXTOR that the relative frequency between the mode and the helical field is important in determining the field penetration [5,6], being in agreement with theoretical results [7][8][9].…”
Section: Introductionsupporting
confidence: 68%
“…(a) Helical field penetration: For the plasma being originally stable to tearing modes, an applied resonant helical field (or error fields of experimental devices) can penetrate through the resonant surface and generate a magnetic island there [1][2][3][4][5][6][7][8][9]. Recently it was shown on TEXTOR that the relative frequency between the mode and the helical field is important in determining the field penetration [5,6], being in agreement with theoretical results [7][8][9].…”
Section: Introductionsupporting
confidence: 68%
“…However, the relation is more complicated in tokamak plasmas, because of shielding or amplification, and poloidal harmonic coupling. Experiments have found that the critical amplitudes of the external field or the external current are approximately linear with locking densities [1][2][3][4][5][6], and also some theories have expected the positive correlation between the critical field and the locking density [10][11][12][13]. However, the approximation of the external resonant field for the resonant field driving islands has been often unsuccessful to find the correlation.…”
Section: Destruction Of Flux Surfaces and Plasma Lockingmentioning
confidence: 99%
“…However, a significant degradation of performance in tokamak plasmas are observed for nonaxisymmetric magnetic perturbations as small as δB/B 0 ∼ 10 −4 . [1][2][3][4][5][6]. Tokamaks are difficult to build without such small errors.…”
Section: Introductionmentioning
confidence: 99%
“…The energy δW = (1/2) δ j ·δ Ad 3 x and the toroidal torque 3 x are produced by external perturbations, where δ j is the perturbed current, δ A is the perturbed vector potential, δ B is the perturbed field, andẑ is the symmetry axis of the tokamak. By integrating by parts for δW and τ ϕ , the perturbed energy and torque can be related to the total normal field at the boundary and the external currents producing the total normal field.…”
Section: Exact Relation For Plasma Response and Implicationmentioning
confidence: 99%